Effects of Vitamin D and Calcium for the Prevention of Osteoporosis at Various Stages of Life of Laying Hens-Review - Duran, Mariana Rodriguez; Chen, Chongxiao; Kim , Woo Kyun (International Journal of Poultry Science, 2018)
Laying hens have been selected for high egg production in a prolonged period. This has negatively affected the health of laying hens, specifically in weakening their bones to the point of developing osteoporosis. Nutrients such as vitamin D and calcium have been studied in order to find a prevention for osteoporosis. The objective of this review was to examine the effects of these nutrients on bone turnover in laying hens in order to find a prevention for osteoporosis through nutritional strategies. Several studies have demonstrated that particulate forms of calcium enhance the absorption of calcium, and thus incorporation of calcium into the bone. Vitamin D has been shown to play a decisive role in blood calcium concentration, and osteoclast activity to break down bone; however, vitamin D continues to play a critical role in laying hen reproduction and is thus necessary. Further research should be done on the ideal concentration of particulate calcium sources and vitamin D in laying hens in order to maintain healthy bone strength and metabolism during the egg laying period.